Perkembangan Struktur Geologi Bawah Permukaan Berdasarkan Hasil Analisis Data Gaya Berat Di Utara Kendari, Sulawesi Tenggara; Implikasinya Terhadap Kemungkinan Terdapatnya Sumber Daya Geologi - D.A Nainggolan (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The result of gravity measurement in the studied area, which is mainly covered by ophiolite, has an anomaly value of ranging from -8 to 86 mgal. Geological and tectonical development of the area have similarities with the east arm of Sulawesi. The presence of hydrocarbon in the Batui quadrangle might be possible to be preserved in this region. Interpretation of the anomaly patterns, subsurface profile models, including the geological structures depict the geological processes, tectonics and its relationship with natural resources. The qualitative analysis results of residual and Bouguer anomalies indicate that the structures in the researched area mainly have northwest - southeast and southwest â€“ northeast directions. Meanwhile, the quantitative analyses of three subsurface model profiles show the presence of two kinds of sedimentary rock with the density of 2.20 gr/cc and 2.35 gr/cc.Â Keywords : gravity, hydrocarbon deposit, Bouguer anomaly, Kendari